Improving Oral Bioavailability of Meloxicam: Development and Characterization of Solid Dispersions - Ratan , Rajeev; Malik , Jitendra; Singh, Gyan; Kumar, G Pawan; Singh, Surendra Pratap; Tiwari, Anadi; Gupta, Prachi (Journal of Biomedical and Pharmaceutical Research, 2024)
This study investigated the development of a solid dispersion to improve the solubility and dissolution of meloxicam, a poorly water-soluble drug. Meloxicam is used to treat pain and inflammation in various conditions. The challenge was to enhance the drug’s oral bioavailability by overcoming its low solubility. Two approaches were explored: 1. Kneading method with Poloxamer 407: This method resulted in a formulation with significantly improved solubility compared to the pure drug. Solvent evaporation method with PVP K-30: While this method offered satisfactory solubility enhancement, it was not as effective as the kneading method with Poloxamer 407.Following the development of the optimized solid dispersion, a suspension formulation was prepared using various suspending agents. The optimized drug formula was then incorporated into the suspension mix. Characterization studies confirmed compatibility between the drug and excipients. FT-IR analysis showed no interaction between the drug and the carriers. Scanning electron microscopy (SEM) revealed a change in meloxicam particle morphology from crystalline to a more amorphous form, indicating a reduction in particle size and a potential explanation for the improved dissolution profile. The dissolution profile of the solid dispersion suspension prepared by the kneading method with Poloxamer 407 outperformed the one prepared with the solvent evaporation method and PVP K-30.This study demonstrates the effectiveness of the kneading method with Poloxamer 407 in developing a solid dispersion of meloxicam with enhanced solubility and dissolution. The optimized formulation exhibited good stability, acceptable drug content and release, and satisfactory rheological properties. This approach has the potential to improve the bioavailability of meloxicam and lead to a more effective oral dosage form. Keywords: Oral Bioavailability, Meloxicam:, Solid Dispersions , FT-IR analysis, SEM